Perspective: white space networking with wi-fi like connectivity - Chandra, Ranveer; Moscibroda, Thomas (Computer Communications Review, 2019)
This paper, titled White Space Networking with Wi-Fi like Connectivity received the best paper award at ACM SIGCOMM 2009. Since then, it has led to new research, a new IEEE standard, new governmental regulations, and a new industry. The work also laid the foundation for new rural connectivity initiatives, connecting rural schools, hospitals, and libraries in Africa, Asia, and America.